Implementasi Kebijakan Beras Daerah Dalam Pengentasan Kemiskinan Di Kabupaten Malinau Provinsi Kalimantan Utara - Hernando, Hady; Dadang Suwanda, Dadang Suwanda; Tjenreng, M. Zubakhrum B. (UIR Press, 2024)
The aim of this research is to analyze the Implementation of Regional Rice Policy in Alleviating Poverty in Malinau Regency, North Kalimantan Province and identify inhibiting and supporting factors for the Implementation of Regional Rice Policy in Alleviating Poverty in Malinau Regency, North Kalimantan Province. This research uses a qualitative descriptive research design, adapting the theory of Implementation as a Political and Administrative Process, proposed by Merilee S. Grindle 1980. This qualitative research uses a triagulation analysis method for data produced through observation studies, interviews and documentation. The research results show 1) The success of policy implementation in terms of process has been carried out well this is shown in the process of grain being purchased from farmers through Perusda Intimung and then managed and packaged into regional rice products in Malinau Regency to the distribution of rice to target beneficiary households (RTS-PM) and The success of the policy objectives has been implemented well in the context of the financial resources managed for the RASDA program amounting to 5,000,000,000 (five billion rupiah) from the Malinau Regency Regional Budget and Revenue (APBD); 2) Policy Implementation (Implementability) in terms of policy content and implementation environment is also good, this is proven by the systematic policy of rules, standards and policy objectives which have been regulated in various regulations ranging from regional regulations, regent regulations and even technical implementation guidebooks. Apart from that, the benefits of this rice subsidy have been felt by the community in providing food supplies and reducing poverty rates in Malinau Regency in line with the high commitment of the Regional Government which has made this Regional Rice Policy an innovative regional program that is sustainable and continues to be improved.